Hydrostatic Pressure versus Passive Diffusion: A Split-Face Comparative Analysis of Intradermal Injection and Microneedling-Assisted Delivery of Botulinum Toxin Type A for Facial Pore Refinement - Jill N Pairunan; Marlyn Grace Kapantow; Ferra Olivia Mawu (HM Publisher, 2026)
Background: Enlarged facial pores, medically termed dilated pilosebaceous follicles, represent a prevalent aesthetic concern driven by seborrhea, follicular hypertrophy, and loss of perifollicular elasticity. Microbotox, the intradermal administration of dilute OnabotulinumtoxinA (BoNT-A), targets these mechanisms through sebosuppression and arrector pili inhibition. However, the optimal delivery vehicle—active intradermal injection versus passive microneedling-assisted transport—remains debated regarding clinical delivery efficiency. Case presentation: A 23-year-old female with Fitzpatrick Skin Type IV, severe pore enlargement (Kim’s Score 5), and seborrhea participated in a split-face comparative study. The right cheek received standard intradermal microdroplet injections of BoNT-A (20 U diluted in 1.0 mL saline). The left cheek underwent automated microneedling at a depth of 2.0 mm immediately followed by topical application of the same BoNT-A solution. Evaluation was performed at baseline, Day 7, and Day 14 using blinded clinical scoring and digital dermoscopic analysis. At Day 14, the intradermal injection side demonstrated superior pore reduction (Kim’s Score 5 to 3) compared to the microneedling side (Score 5 to 4). Digital quantification confirmed a 45% reduction in mean pore diameter on the injected side versus 18% on the microneedling side. While both modalities effectively reduced sebum scores to 1, the microneedling side exhibited delayed pore refinement, likely attributed to post-traumatic edema and the wash-out effect of blood flow antagonizing passive diffusion. Conclusion: Direct intradermal injection provides superior clinical delivery efficiency for BoNT-A, resulting in more rapid and significant pore contraction. Microneedling-assisted delivery, particularly at depths inducing vascular injury, acts as a secondary adjunct for textural remodeling but is inferior for immediate pharmacological delivery of large-molecule toxins.